2019
DOI: 10.3847/1538-4357/ab5526
|View full text |Cite
|
Sign up to set email alerts
|

Spatially Resolved Properties of Galaxies from CANDELS+MUSE: Radial Extinction Profile and Insights on Quenching

Abstract: Studying the internal processes of individual galaxies at kilo-parsec scales is crucial in enhancing our understanding of galaxy formation and evolution processes. In this work, we investigate the distribution of star formation rate (SFR), specific SFR (sSFR), and dust attenuation across individual galaxies for a sample of 32 galaxies selected from the MUSE-Wide Survey at 0.1 < z < 0.42 with a dynamic range in stellar masses between 10 7.7 and 10 10.3 M . We take advantage of the high spatial resolution of the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 20 publications
(32 citation statements)
references
References 52 publications
9
23
0
Order By: Relevance
“…Of these quantities, the median local A V, gas depends most strongly on stellar mass: its average value increases for increasing stellar mass. This finding is in agreement with those of other authors, who report higher average values for the local A V, gas for higher-mass galaxies (Nelson et al 2015a;Jafariyazani et al 2019). By contrast, the median local A V, stars does not change appreciably between each stellar mass category (although see González Delgado et al 2015 andGoddard et al 2016, both of whom do find higher average values for A V, stars in galaxies with higher stellar masses.…”
Section: Average and Radial Variation Of Dust Attenuation: Dependence On Stellar Masssupporting
confidence: 92%
See 3 more Smart Citations
“…Of these quantities, the median local A V, gas depends most strongly on stellar mass: its average value increases for increasing stellar mass. This finding is in agreement with those of other authors, who report higher average values for the local A V, gas for higher-mass galaxies (Nelson et al 2015a;Jafariyazani et al 2019). By contrast, the median local A V, stars does not change appreciably between each stellar mass category (although see González Delgado et al 2015 andGoddard et al 2016, both of whom do find higher average values for A V, stars in galaxies with higher stellar masses.…”
Section: Average and Radial Variation Of Dust Attenuation: Dependence On Stellar Masssupporting
confidence: 92%
“…This behaviour suggests that the radial gradients seen in the local A V, gas , both in this work and in other work (e.g. Nelson et al 2015a;Jafariyazani et al 2019) cannot be attributed to a radial gradient in the diffuse ISM alone.…”
Section: Average and Radial Variation Of Dust Attenuation: Dependence On Stellar Masssupporting
confidence: 64%
See 2 more Smart Citations
“…morphology, existence of a bar). Jafariyazani et al (2019) found a spatially resolved MS in galaxies at 0.1 < z < 0.42 observed with MUSE. Medling et al (2018) estimated the MS from ∼ 800 galaxies in the Sydney AAO Multi-object Integral Field Galaxy Survey (SAMI, Croom et al 2012) at z < 0.1, finding a slope of 1.0.…”
Section: Introductionmentioning
confidence: 69%